2017
DOI: 10.1038/ncomms15618
|View full text |Cite
|
Sign up to set email alerts
|

DNA exonuclease Trex1 regulates radiotherapy-induced tumour immunogenicity

Abstract: Radiotherapy is under investigation for its ability to enhance responses to immunotherapy. However, the mechanisms by which radiation induces anti-tumour T cells remain unclear. We show that the DNA exonuclease Trex1 is induced by radiation doses above 12–18 Gy in different cancer cells, and attenuates their immunogenicity by degrading DNA that accumulates in the cytosol upon radiation. Cytosolic DNA stimulates secretion of interferon-β by cancer cells following activation of the DNA sensor cGAS and its downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
1,204
6
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,361 publications
(1,343 citation statements)
references
References 39 publications
44
1,204
6
10
Order By: Relevance
“…Seminal studies using breast cancer models showed that the DNA exonuclease 3 repair exonuclease 1 (TREX1) inhibits immune activation 45,46 . TREX1 is induced by radiation doses above 12–18 Gy in different colorectal carcinoma and breast cancer cell lines, and it attenuates immunogenicity by degrading double-strand DNA that accumulates in the cytosol upon radiation 47 . Further investigations of dosage and combinations of radiotherapy with immunotherapy are needed to determine the optimal thresholds or range 48 .…”
Section: Boosting the Abscopal Effectmentioning
confidence: 99%
“…Seminal studies using breast cancer models showed that the DNA exonuclease 3 repair exonuclease 1 (TREX1) inhibits immune activation 45,46 . TREX1 is induced by radiation doses above 12–18 Gy in different colorectal carcinoma and breast cancer cell lines, and it attenuates immunogenicity by degrading double-strand DNA that accumulates in the cytosol upon radiation 47 . Further investigations of dosage and combinations of radiotherapy with immunotherapy are needed to determine the optimal thresholds or range 48 .…”
Section: Boosting the Abscopal Effectmentioning
confidence: 99%
“…Notably, in ALT cancer cells cytosolic DNA sensing is defective, suggesting that loss of cell-intrinsic self-DNA sensing is requirement for transformation and maintenance of ALT cells. Mammary tumor cells subjected to increasing doses of radiation therapy also accumulate DNA in the cytoplasm, which correlates with cGAS-mediated expression of IFN-I and IFN-I stimulated genes [58]. TREX1 is an important regulator of the intrinsic process, as it is up-regulated at high doses of radiation and drives attenuation of the immunogenic signal.…”
Section: Cancer Cancer Therapy and Genotoxic Stressmentioning
confidence: 99%
“…1823 On the contrary, a recent study suggests that 3 × 8 Gy may be optimal. 24 Clinically, abscopal tumor lesion regression remains rare, most likely because comparable super-hypofractionated protocols (fractions of >5 Gy) are rarely used in the radiotherapeutic routine.…”
Section: Introductionmentioning
confidence: 99%